PROVERBS AND PHRASEOLOGICAL UNITS AS A MEANS OF REFLECTING NATIONAL CULTURAL VALUES (SCIENCE TIME JOURNAL, 2026)
The article examines proverbs and phraseological units as reflections of national culture and worldview. Based on English, Russian, and Uzbek examples, their linguocultural features and role in preserving cultural values are analyzed. Special attention is given to how fixed expressions transmit traditions, moral norms, and the historical experience of a nation. The study highlights the importance of language as a means of preserving and transmitting cultural heritage.